Mapping underground layers in the super arid Gidron Wadi using electrical resistivity tomography (ERT). (October 2015) - Winters, Gidon; Ryvkin, Ina; Rudkov, Tali; Moreno, Ziv; Furman, Alex
Abstract: Along the arid Arava, southern Israel, acacia trees are considered keystone species. Based on survival of acacias through drought years that have not seen a single rainfall or flood, it is assumed that acacias endure the local harsh conditions by drawing water from deep underground water reservoirs. Studying water use of acacias has so far been done by exposing root systems or by isotopic water measurements, both problematic methods. We present a new application of a two-dimensional direct current electrical resistivity tomography (ERT) to measure the electrical resistivity of the subsurface. We applied the ERT device to two fixed 100 m transects cutting across (north-south) and along (west-east) the super arid Gidron Wadi during March, April and August 2013. An inversion model was used to create a map of electrical resistivity of the layers below ground, an indirect indicator of the underground water content. We identified a conductive layer located at ∼7–10 m below ground in all surveys. Although we could not identify changes to this apparent perched aquifer, such a layer may be a secondary source of water for acacias that can explain their survival in drought years. Further ERT-aided studies are needed to correlate acacia distribution and ecophysiological state with perched aquifers, even if quantitative analysis of their replenishment in such desert environments is not trivial. Highlights: Studying water use of acacia trees in arid regions is problematic. We applied electrical resistivity tomography (ERT) to an ephemeral arid river. We identified a conductive layer ∼7–10 m below ground, possibly a perched aquifer. Layer may act as a secondary source of water for acacias and explain their survival.